Controlling parenting and executive functioning in children born preterm - Toscano, C. (2022)
This study investigated the relations between mothers’ and fathers’ controlling behaviors and the executive functioning of children born preterm. Sixty-eight preterm children and their parents were assessed when the children were 3 ½ years old. The executive functioning was measured using the Headto-Toes-Task and controlling parenting behaviors were measured through a standardized observation of a parent-child interaction. Hierarchical regression analysis showed that both mothers’ and fathers’ controlling behaviors were associated with worse child executive functioning performance, after controlling for the child’s cognitive ability. Findings suggest that both mothers and fathers play an important role in the development of executive functioning of children born prematurely, highlighting the need to consider both parents in the study of and intervention with these children.